Low‐profile and low‐cost transmitarray antenna at 122 GHz based on unit‐cells with 1‐bit phase resolution. Issue 24 (3rd November 2020) - Frank, M.; Lurz, F.; Weigel, R.; Koelpin, A.
Abstract : This Letter presents the design of a low‐profile and low‐cost transmitarray antenna operating at 122 GHz. The transmitarray design is based on unit‐cells with 1‐bit phase resolution. A single RO4350B substrate layer is used to form the unit‐cells resulting in a total thickness of 0.326 mm. A wideband shift in the transmission phase of 180 ° is generated by rotating one metal layer of the unit‐cell by 180 ° . The simulation of the transmitarray with 30 × 30 elements and a feed distance of 35 mm shows a maximum directivity of 28 dBi at 122 GHz. Steering angles of 0 ° and 15 ° are investigated. Measurements of the fabricated transmitarrays are performed with an open waveguide and a package antenna as feed showing similar results but slightly different maximum relative gain values of 11.8 and 9.5 dB for the 0 ° version. The measured main beam directions are in good agreement with the simulations and the design values.